The Influence of Collateral and Business Conditions on Non-Performing Loans with Debtor Character as a Moderating Variable at PT. BPR Duta Paramarta - Hamonangan Justinus Gultom; Erna Susilawaty Sebayang (LP2M IAIN Palopo, 2025)
This study investigates the influence of collateral and business conditions on non-performing loans (NPLs), with debtor character as a moderating variable, at PT. BPR Duta Paramarta. Using a quantitative explanatory design, data were collected from 100 debtors through loan records and structured questionnaires. Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 was employed to analyze the relationships. The results indicate that collateral (β = 0.424, p < .001) and business conditions (β = 0.362, p = .001) significantly reduce the probability of NPLs. The moderating effect of debtor character on collateral was insignificant (β = –0.079, p = .254), suggesting that collateral remains the dominant predictor regardless of behavioral attributes. However, debtor character significantly moderated the relationship between business conditions and NPLs (β = 0.274, p = .011), amplifying repayment success when favorable traits are present. These findings extend the 5C credit evaluation model and highlight the importance of integrating behavioral assessment in rural banking risk management.